Association of Biopsychosocial Factors With Degree of Slump in Sitting Posture and Self-Report of Back Pain in Adolescents : A Cross-Sectional Study - O'Sullivan, Peter; Smith, Anne; Beales, Darren; Straker, Leon (American Physical Therapy Association, 2011)
Background: Conflicting evidence exists regarding relationships among sitting posture, factors that influence sitting posture, and back pain. This conflicting evidence may partially be due to the presence of multiple and overlapping factors associated with both sitting posture and back pain.Objective: The purpose of this study was to determine whether the degree of slump in sitting was associated with sex and other physical, lifestyle, or psychosocial factors. Additionally, the relationship between the report of back pain made worse by sitting and the degree of slump in sitting and other physical, lifestyle, or psychosocial factors was investigated. Design: This was a cross-sectional study. Methods: Adolescents (n=1,596) completed questionnaires to determine lifestyle and psychosocial profiles and the experience of back pain. Sagittal sitting posture, body mass index (BMI), and back muscle endurance (BME) were recorded. Standing posture subgroup categorization was determined. Results: Multivariate analysis revealed that the most significant factor associated with the degree of slump in sitting was male sex, followed by non-neutral standing postures, lower perceived self-efficacy, lower BME, greater television use, and higher BMI. Multivariable analysis indicated poorer Child Behaviour Checklist scores were the strongest correlate of report of back pain made worse by sitting, whereas degree of slump in sitting, female sex, and BME were more weakly related.Limitations: Causality cannot be determined from this cross-sectional study, and 60% of sitting posture variation was not explained by the measured variables. Conclusions: Slump in sitting was associated with physical correlates, as well as sex, lifestyle, and psychosocial factors, highlighting the complex, multidimensional nature of usual sitting posture in adolescents. Additionally, this study demonstrated that a greater degree of slump in sitting was only weakly associated with adolescent back pain made worse by sitting after adjustment for other physical and psychosocial factors.